Pelatihan Pembuatan LKPD Berbasis Live Worksheet di SMA Dharma Amiluhur - Nafida Hetty Marhaeni; Ichlasia Ainul Fitri (Madani : Indonesian Journal of Civil Society, 2023)
The purpose of this service is to provide training to teachers at Dharma Amiluhur High School on how to convert Student Worksheets (LKPD) into electronic LKPD (E-LKPD) with the help of the live worksheet website. The subjects in this service were 25 teachers at Dharma Amiluhur High School. While the materials taught are the making of LKPD and the conversion of LKPD into E-LKPD. The results of the service show that there is an increase in the teacher's knowledge of making teaching materials and making electronic teaching materials using the live worksheet website. Furthermore, the results of the evaluation carried out using a questionnaire showed that overall there was an increase in the indicators of successful service implementation by 28%. This indicator includes knowledge of teaching materials, knowledge of live worksheet websites, knowledge of live worksheet features, knowledge of LKPD design, and knowledge of the stages of making LKPD and electronic LKPD. This means that the evaluation of the implementation of community service has shown good results because each indicator of success has increased and there has even been a very significant increase. The teachers at the school also really hope that there will be workshops on other topics while maintaining technology-based topics.